Incorporation of High Loss-on-ignition Fly Ash in Producing High-strength Flowable Mortar - Ngo, Si-Huy; Nguyen, Ngoc Tan; Mai, Thi-Hong (Periodica Polytechnica Civil Engineering, 2024)
A large amount of fly ash with a high loss on ignition (over the maximum allowance value stipulated by ASTM C618) is being released and increasing daily in Vietnam. The recycling of this fly ash is still limited, while a big remaining part is disposed of in storage yards, causing environmental pollution. On the other hand, the demand for high-strength mortar as a repair material is increasing for high-rise buildings and important projects, gradually depleting natural resources. However, the application of this fly ash in the production of mortar is restricted in the literature. In this study, local fly ash with a high loss on ignition is used to replace 0%, 15%, 30%, 45%, and 60% cement content in producing high-flowability and high-strength mortar. Changes in the fresh and hardened mortar properties were systematically investigated using samples produced with various fly ash contents. Test results indicate that the effect of impurities in fly ash on the mortar’s workability can be neglected due to the spherical shape of fly ash. The unit weight, thermal conductivity, and drying shrinkage of mortars decreased with increasing fly ash content. Although some other properties of mortar are reduced due to the use of high loss-on-ignition fly ash, all mortars produced in this study still showed good quality with the presence of silica fume. In addition, the relationships between compressive strength and flexural strength with ultrasonic pulse velocity were established to predict the strength of mortar in a non-destructive method.